AN ANALYSIS ON VALIDITY AND RELIABILITY OF TEST ITEMS IN FINAL SEMESTER EXAMINATION - Rahmi, Aulia; Sutapa Y, Y. Gatot; Suhartono, Luwandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract The main purpose of this research was to get information about the quality of a teacher-made test for semester final examination from Science and Social majors of eleventh grade of SMA Negeri 5 Pontianak that focused on validity, reliability, item discrimination, item difficulty, and distractor. Case study was used in this study. The test items were teacher-made that consisted of 50 items with 321 test takers. Based on content validity analysis, all the test items matched the test blueprint therefore the test was effective and efficient to measure students’ knowledge from both majors. The result was supported by reliability analysis that showed 0.817 and it was categorized as very good for a classroom test. Item difficulty analysis also showed good results that both majors had moderate items as the highest number in the test and the means were also in normal distribution. The finding from distractor analysis was also balance that means still have good effect on the test quality. It is suggested that to discard or revise the distractors which did not function well so the test items are not too difficult or too easy, therefore the revised or new items can be used along with the items which already had good quality in terms of item difficulty, item discrimination, and distraction in the future. Keywords: Semester Final Examination, Validity, Reliability, Test, Item Analysis